Cement augmentation of metastatic lesions in the proximal femur can improve bone strength. (April 2020) - Sas, Amelie; Van Camp, Dries; Lauwers, Bert; Sermon, An; van Lenthe, G. Harry
Abstract: Prophylactic treatment is advised for metastatic bone disease patients with a high risk for fracture. Femoroplasty provides a minimally invasive procedure to stabilize the femur by injecting bone cement into the lesion. However, uncertainty remains whether it provides sufficient mechanical strength to the weight-bearing femur. The goal of this study was to quantify the improvement in bone stiffness, failure load and energy to failure due to cement augmentation of metastatic lesions at varying locations in the proximal femur. Eight pairs of human cadaveric femurs were mechanically tested until failure in a single-leg stance configuration. In each pair, an identical defect was milled in the left and right femur using a programmable milling machine to simulate an osteolytic lesion. The location of the defects varied amongst the eight pairs. One femur of each pair was augmented with polymethylmethacrylate, while the contralateral femur was left untreated. Digital image correlation was applied to measure strains on the bone surface during mechanical testing. Only femurs with a critical lesion showed an improvement in failure load and energy to failure due to augmentation. In these femurs, bone strength improved with 28% (±17%) on average and energy to failure with 58% (±41%), while stiffness did not show a significant improvement. The strain measurements from digital image correlation showed that cement augmentation reinforced the lesion, resulting in reduced strain magnitudes in the bone tissue adjacent to the lesion. The results indicate that femoroplasty may be an effective treatment to prevent fractures in several metastatic bone disease patients. However, the large scatter in the data clarifies the need for developing strategies to identify those patients who will benefit the most from the procedure.